Effects of heavy metal ions on N-nitrosodimethylamine (NDMA) formation. Issue 74 (25th July 2016) - Liu, Yameng; Liu, Yongdong; Zhong, Rugang; Peng, Bin; Schaefer, III, Henry F.
Abstract : The mechanism of NDMA formation as affected by heavy metal complexes [MONO] + (M = Cd, Pb, Hg) was investigated using density functional theory (DFT). Three possible NDMA formation pathways are discussed. Abstract : Heavy metals as pollutants cause threats to the environment and human health. Nitrosodimethylamine (NDMA) is a probable human carcinogen. In this research, the mechanism of NDMA formation as affected by heavy metal complexes [MONO] + (M = Cd, Pb, Hg) was investigated using density functional theory (DFT). The results show that the formation of NDMA from the reaction of DMA with NO2 − can be catalyzed by the heavy metal complex. Three possible NDMA formation pathways are obtained. Moreover, we find that one molecule of [MONO] + (Pathway 1, M = Cd, Hg; Pathway 2, M = Cd, Pb, Hg) reacts directly with DMA via two different pathways, forming different transition states to produce NDMA. Another mechanism (Pathway 3) shows that two [CdONO] + molecules will produce N2 O3 which reacted with DMA to give NDMA. These findings will expand our understanding of the environmental significance of heavy metal ions and perhaps help develop efficient methods to prevent the formation of carcinogenic nitrosamines.